Comparing the Efficiency of Single versus Dual Ultrasonic Devices for Metallic Post Removal in Endodontic Retreatment: A Clinical Study - Pereira, Key Fabiano Souza; Junqueira-Verardo , Lia Beatriz; Zafalon , Edilson José; Tomazinho , Luiz Fernando; Nascimento , Vanessa Rodrigues do; Bastos , Hugo José Santos; Otani, Alex Yoshiharu (Iranian Endodontic Journal, 2024)
Introduction: Ultrasonic vibration for metallic post removal seems to be a unanimous choice between endodontists and general practitioners for providing the best results and having the highest safety. This study compared the time required by ultrasonic vibration for removing metallic post (MP) when 1 or 2 ultrasonics devices are used. Materials and Methods: One hundred and fifteen teeth with MPs from 105 patients, indicated for nonsurgical endodontic retreatment were divided into 2 groups according to the number of ultrasonic devices used (G1-1 device) and (G2-2 devices). In G1, the MP was worn with a transmetal bur, alongside the wear of the cement line (around 2 mm deep). Then, an ultrasonic tip attached to an ultrasonic unit, with a power of 100% was activated at the level of the post, with constant water spray at a level of 1 mm above the axial surface of the tooth. The position of the tip was changed between buccal and lingual surfaces every 10 seconds until the MP was removed. In G2 the same procedures were performed as described in G1, but two ultrasonic tips were activated simultaneously at buccal and lingual surfaces until the MP was removed. The vibration time necessary for removing each MP was recorded using a chronometer. Results: The mean time was 131.10±29.68 seconds (mean±standard error of the mean) for MP removal using one ultrasonic device, and 24.86±6.88 seconds for two devices. The time required for MP removal using two ultrasonic devices was significantly less than when using one ultrasonic device (P<0.001). Conclusion: The technique with 2 ultrasonic devices proved to be more efficient than the one using only 1 ultrasonic device.